An assessment of the impact of educational interventions on hand hygiene compliance - Husband, Carla; McMillan, Abbie; Sweeney, Lauren (Veterinary Evidence, 2020)
PICO question In small animal veterinary professions, does implementation of an educational intervention, when compared to no intervention, improve hand hygiene compliance? Clinical bottom line Category of research question Treatment The number and type of study designs reviewed Three papers were critically appraised. They were all prospective observational cohort studies Strength of evidence Weak Outcomes reported Two out of the three papers did not find educational implementation to have a statistically significant positive effect on hand hygiene compliance (HHC) in small animal veterinary professionals Conclusion The veterinary evidence reviewed does not provide strong justification for the use of education in the improvement of HHC in small animal practice. This contrasts with extensive human evidence which supports the use of educational interventions (Helder et al., 2010). However, a limited veterinary knowledge base in the field of HH, combined with the flawed methodologies of the appraised literature, suggests that this finding is not representative of the effect education could have on HHC. The conclusion drawn from the evidence assessed within this Knowledge Summary is that educational interventions are not significantly linked to an improvement in HHC within a small animal veterinary setting. When considering the volume of human evidence which supports education as a tool to improve HHC, the authors suggest this Knowledge Summary should be repeated in the future when additional veterinary evidence is available to reassess the conclusion drawn How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision-making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.